Experience of caries and tooth loss in rural citrus workers in Northeast Brazil - Alvim-Pereira, Fabiano; Menezes, Vanessa Nascimento; Lima, Ricardo Barbosa; Rocha, Daniel Maranha da; da Rocha, Milena Cerqueira; de Mendonça, Adriano Augusto Melo (Journal of Health & Biological Sciences, 2021)
Objective: To evaluate the experience of caries and tooth loss in rural citrus workers in Northeast Brazil. Methods: This was a cross-sectional, quantitative, and descriptive study carried out using a non-probabilistic sample of rural citrus workers linked to the Occupational Health Reference Center. Generalist and dental questionnaires were applied and clinical examinations were performed by two calibrated examiners on 619 participants in Basic Health Units to establish the sample DMFT index and to detail their characteristics of interest. Results: The sample was predominantly male (71%), with young adults between 20 and 40 years (50,9%), with low education (76%) and low income (59,3%). The mean DMFT index of the sample was 14.29 and the component regarding tooth loss (M) 9.97, corresponding to approximately 70% of this value. Moreover, 90,1% of the evaluated participants had losses of at least one dental element and 27,8% had a functional loss with less than 21 teeth in the oral cavity, while 86.3% said they had never attended an oral health service. Of the participants who have already attended, 83,6% were over six months ago, motivated by pain (43,8%) and caries (14,7%). Conclusions: The rural citrus workers evaluated had negative experiences with dental caries and a high rate of functional tooth loss, leading them vulnerable to stomatognathic system imbalances and showing the need for prevention and promotion of oral health.